Assessment of efficacy, safety, and tolerability of 4-n-butylresorcinol 0.3% cream: an Indian multicentric study on melasma - Madan Mohan NT; Gowda A; Jaiswal AK; Sharath Kumar BC; Shilpashree P; Gangaboraiah B; Shamanna M (Dove Medical Press, 2016)
NT Madan Mohan,1 Adarsh Gowda,2 Ashok Kumar Jaiswal,1 BC Sharath Kumar,2 P Shilpashree,1 Bilugumba Gangaboraiah,3 Manjula Shamanna4 1Department of Dermatology, Dr BR Ambedkar Medical College (BRAMC), Bangalore, Karnataka, India; 2Department of Dermatology, 3Department of Community Medicine, Kempegowda Institute of Medical Sciences (KIMS), Bangalore, Karnataka, India; 4Medical Services, Micro Labs Ltd, Bangalore, Karnataka, India Introduction: Melasma is one of the commonly reported pigmentory disorders in the Indian population. Numerous therapeutic modalities are available. However, very few have produced complete satisfactory response. 4-n-Butylresorcinol 0.3% cream has recently been introduced in India as a new hypopigmenting agent. It is a resorcinol derivative and acts by inhibiting both tyrosinase and tyrosinase-related protein-1. Objective: The available published literatures are with 4-n-butylresorcinol 0.1% cream, and there is paucity of clinical studies with 4-n-butylresorcinol 0.3% cream. Furthermore, considering the fact that Indian skin is more prone to irritation with hypopigmenting agents, our study explores the efficacy, safety, and tolerability of 4-n-butylresorcinol 0.3% cream in Indian subjects with melasma. Methods: Fifty-two subjects with melasma participated in this open-label, single arm, observational study. All the patients were advised twice daily application of 4-n-butylresorcinol 0.3% cream for 8 weeks over the areas of melasma. Assessment parameters included modified Melasma Area Severity Index (mMASI) score. Digital photographs of all the patients at baseline, week 4, and week 8 were taken. During this 8-week study period, all the adverse events were observed and recorded. Results: All the 52 subjects completed the study. Out of 52 subjects, 90.38% were females. The mean age of patients was 38.5±7.8 years. Mean ± standard error of MASI score measurements showed a significant decrease from baseline score of 14.73±0.59 to 11.09±0.53 after week 4 (P<0.001) and 6.48±0.43 at week 8 (P<0.001). The digital photographs of the study subjects taken at week 4 and week 8 also showed decrease in melasma pigmentation compared to baseline photograph and correlated with the changes in the mMASI score. The treatment was well tolerated by all the study subjects. No adverse reactions were reported throughout the study period. Conclusion: Our data suggest that the 4-n-butylresorcinol 0.3% cream is safe, effective, and well tolerated in Indian patients with melasma. Keywords: 4-n-butylresorcinol, melasma, topical treatment, tyrosinase inhibitors